2005
DOI: 10.1121/1.1861060
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Absorbers and Diffusers, Theory, design and application

Abstract: Types of absorber 11 2.2 Reverberation control 12 2.2.1 A statistical model of reverberation 17 2.3 Noise control in factories and large rooms with diffuse fields 20 2.4 Modal control in critical listening spaces 22 2.5 Echo control in auditoria and lecture theatresbasic sound propagation models 23 2.5.1 Sound propagation-a wave approach 24 2.5.2 Surface impedance, admittance, reflection coefficient, and absorption coefficient 25 2.6 Absorption in sound insulation-transfer matrix modelling 29 2.6.1 Transfer ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
214
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(226 citation statements)
references
References 0 publications
5
214
0
7
Order By: Relevance
“…The inherent viscothermal losses of an acoustic system combined with wave interference can give rise to perfect absorption, a phenomenon which is of great applied interest in many fields like room acoustics [1,2], duct mufflers [3], aeroacoustic liners [3] and environmental acoustics [4]. In the particular case of a two-port, resonator/waveguide system, it has been shown that Coherent Perfect Absorption (CPA) can be obtained under a so-called critical coupling condition when the two-sided incident waves correspond to an eigenmode of the scattering matrix of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The inherent viscothermal losses of an acoustic system combined with wave interference can give rise to perfect absorption, a phenomenon which is of great applied interest in many fields like room acoustics [1,2], duct mufflers [3], aeroacoustic liners [3] and environmental acoustics [4]. In the particular case of a two-port, resonator/waveguide system, it has been shown that Coherent Perfect Absorption (CPA) can be obtained under a so-called critical coupling condition when the two-sided incident waves correspond to an eigenmode of the scattering matrix of the system.…”
Section: Introductionmentioning
confidence: 99%
“…This BC models a resonating sound absorber such as of a membrane type, characterized by its complex impedance [37] z…”
Section: Resonance Absorbermentioning
confidence: 99%
“…25,26 The reason thicker foams have better sound absorption comes from the particle velocity theory described by Cox. 27 The theory states that significant sound absorption COMPRESSION-MOLDED OPEN-CELL PP FOAMS only occurs where particle velocity is high. High particle velocity will occur in foam farthest away from the rigid wall boundary; hence, thicker samples should have better sound absorption.…”
Section: Effect Of Cell Morphology On Sound Absorptionmentioning
confidence: 99%